Keteladanan Kepemimpinan Hamba Tuhan Upaya Penerapan Kesadaran Pentingnya Beribadah (International Forum of Researchers and Lecturers, 2023)
Exemplary leadership of God's servants in carrying out efforts to raise awareness of the importance of worship. This is very important for society. Provide more understanding and exemplary than God's servant who can influence or make an exemplary example that reflects the basic ministry of Jesus the Messiah who is an example. In this study, there is a symptom that causes church members not to consider worship as important in building public awareness to prioritize worship with the aim of each working and glorifying God in worship. The presence of God's servant in the organization to perform ministry. Services that are carried out humbly can encourage the congregation to pray and provide an understanding of the importance of worship which will change the pattern of life that God really wants.